(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this paper we consider the generalization of the concept of cointegration to non-stationary processes which are not necessarily I(d). Two cases are of special interest. First the case of non-stationary processes which adjust to an equilibrium not necessarily according to a linear adjustment process. Second the case of non-stationary (possibly I(1)) series which co-move according to a non linear or heteroscedastic adjustment process . The non-stationary processes considered here belong to the Kampé de Fériet (KF) class.